1971
DOI: 10.1098/rspb.1971.0062
|View full text |Cite
|
Sign up to set email alerts
|

Cuticle reflectivity and optical activity in scarab beetles: the role of uric acid

Abstract: The iridescent cuticle of certain Rutelino scarab beetles, which is a form optically active and selectively reflects circularly polarized light, incorporates an NH 4 OH -extractable component The ultraviolet absorption spectrum of this component, together with its chromatographic and refractive properties, identify it as uric acid (2,6,8-trihydroxypurine). All species of Plusiotis examined have uric acid in their reflecting layers, as do several species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 18 publications
(28 reference statements)
4
96
1
Order By: Relevance
“…The measured reflectance spectra were modelled with refractive index values that varied between 1.60 and 1.70 (figures 12 and 13), where the latter value is similar to the maximal refractive index values derived for scarab beetle cuticle by Caveney [18] and for C. raja by Noyes et al [10]. The modelling showed that the peak wavelength and amplitude of the reflectance spectra are quite sensitive for the range of the refractive index.…”
Section: Discussion (A) the Refractive Index Of Melanin In Biologicalmentioning
confidence: 99%
See 3 more Smart Citations
“…The measured reflectance spectra were modelled with refractive index values that varied between 1.60 and 1.70 (figures 12 and 13), where the latter value is similar to the maximal refractive index values derived for scarab beetle cuticle by Caveney [18] and for C. raja by Noyes et al [10]. The modelling showed that the peak wavelength and amplitude of the reflectance spectra are quite sensitive for the range of the refractive index.…”
Section: Discussion (A) the Refractive Index Of Melanin In Biologicalmentioning
confidence: 99%
“…[17]). The jewel beetle's multilayers are presumably homogeneous, causing only linear polarization, whereas circular polarization is a dominant feature in scarab beetles [18,20,23,24]. For scarab beetles, Caveney [18] concluded that the reflective layers had a high concentration of uric acid, causing a high refractive index value of about 1.70.…”
Section: Discussion (A) the Refractive Index Of Melanin In Biologicalmentioning
confidence: 99%
See 2 more Smart Citations
“…45), photonic properties do not provide the need for differentiation between these two bicontinuous forms. In the context of the enantiomeric composition and the question if the molecular chirality of chitin contributes to the selection of the enantiomeric type, it is useful to consider a structurally unrelated chiral manifestation of chitin: the Bouligand structure observed in a variety of beetles (17,19,48); in these beetles, which are strongly circularly polarizing (19,49,50) and where the chirality is widely believed to result from a process analogous to a cholesteric phase formation, only the LH enantiomer is observed. Interestingly, in the analogous phase found in the cellulose structure of a particular plant, Pollia condensata, both enantiomers are observed (18).…”
Section: Discussionmentioning
confidence: 99%